PENGARUH AUDIT SUMBER DAYA MANUSIA TERHADAP EFEKTIVITAS ORGANISASI PADA PT (PERSERO) SURVEYOR INDONESIA SURABAYA AREA - Patrianus Khristian Sumule (Universitas Tribhuwana Tunggadewi, 2012)
This research aims to clarify the effect of human resource audit of the effectiveness of the organization at PT. Surveyor Indonesia Surabaya Area and to describe the most dominant factor of the independent variables of human resource audit consisting of variable audit function of human resources, audit of managerial compliance and audit of employee satisfaction in influencing organizational effectiveness at PT. Surveyor Indonesia Surabaya Area. It is expected that the company audits consistently human resource periodically in order to keep productivity of employees improved from time to time.